2015
DOI: 10.1111/add.13202
|View full text |Cite
|
Sign up to set email alerts
|

Increasing compliance with alcohol service laws in a developing country: intervention trial in the Kingdom of Bhutan

Abstract: A multi-sector programme to improve compliance with legal restrictions on serving alcohol in Bhutan appeared to have a modest effect but even after the programme, in two-thirds of the occasions tested, the laws were broken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…It is unclear if the intervention would be as effective in other communities and states or outside the U.S., especially where alcohol controls are weak [39]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear if the intervention would be as effective in other communities and states or outside the U.S., especially where alcohol controls are weak [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Second, the study was conducted in 16 midsized communities in four states of the USA. It is unclear if the intervention would be as effective in other communities and states or outside USA, especially where alcohol controls are weak [39].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Thimphu revealed only 20% compliance with alcohol service laws which prohibit sales outside specified hours and to intoxicated or underage patrons 16. There has been rapid growth in the number of such outlets; there are now over 1000 in Thimphu alone: one for every 80 residents over 14 years of age 17.…”
Section: Discussionmentioning
confidence: 99%
“…Bhutan's alcohol policies, introduced in the last two decades, are evidence based in many respects—alcohol sales are limited to 1–10 pm Wednesday–Monday, and serving minors (<18 years old) or intoxicated patrons is illegal—but enforcement is poor. A 2013 mystery shopper program using covert observation revealed a baseline of only 20% compliance with these laws . Compliance improved modestly after owners and managers were educated about the law and encouraged to modify their service practices .…”
Section: Alcohol Policymentioning
confidence: 99%
“…A 2013 mystery shopper program using covert observation revealed a baseline of only 20% compliance with these laws . Compliance improved modestly after owners and managers were educated about the law and encouraged to modify their service practices .…”
Section: Alcohol Policymentioning
confidence: 99%